ANTIBIOFILM ACTIVITY OF FIVE NATIVE PLANTS OF KALIMANTAN ISLAND AGAINST Staphylococcus aureus - Wibowo, Joko Priyanto; Wahid, Abdul Rahman; Paramitha, Dewi Setya; Wewengkang, Restu Dara; Nurrahmah, Medina (Universitas Muhammadiyah Magelang, 2025)
Infections caused by Staphylococcus aureus are an increasing concern in the healthcare sector, particularly due to the rise of antibiotic-resistant strains. Natural products provide a promising alternative source for discovering new antibacterial and antibiofilm agents. This study aimed to evaluate the antibiofilm activity of five plant species natives to Kalimantan Island against S. aureus. Plant materials were extracted using the ultrasound-assisted extraction (UAE) method with 70% ethanol at 40 kHz and temperature of 30 °C for 30 minutes. Phytochemical screening was performed using standard qualitative tests to detect major secondary metabolite groups, including alkaloids, flavonoids, tannins, saponins, and terpenoids. The antibiofilm assay was carried out using a spectrophotometric microplate method, where biofilm formation was quantified in the presence of plant extracts (500 ppm) compared to negative control (solvent). Data were analyzed statistically using ANOVA (p < 0.05) followed by post-hoc tests to determine significant differences among samples. Among the tested extracts, the gelinggang extract exhibited the strongest antibiofilm effect, inhibiting biofilm formation by 84.39 ± 7.21 %, followed by sangkareho (70.63 ± 7.29 %), kratom (66.54 ± 6.11 %) and matoa (58.36 ± 5.91 %). While, limpasu showed the weakest antibiofilm activity (18.22 ± 1.21 %) in this study. The observed activity may be attributed to the presence of phenolic and flavonoid compounds known to disrupt quorum sensing and biofilm matrix synthesis. These findings highlight the potential of Kalimantan’s native plants, particularly gelinggang, as promising sources of natural antibiofilm agents for combating antibiotic-resistant S. aureus infections.